2019
DOI: 10.1016/j.evalprogplan.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the feasibility of a community intergenerational physical activity intervention for kinship families: Professional stakeholders’ perspectives

Abstract: Over the past 30 years, the number of grandparents who are raising grandchildren has increased (Dolbin-MacNab & Traylor, 2016;Lugaila, 1998;Simmons & Dye, 2003; U.S. Census Bureau, 2011). This increase is due to a variety of factors including parental child abuse, neglect, drug abuse, economic hardship (Taylor, Livingston, Wang, & Dockterman, 2010), divorce, and death (Gleeson, et al., 2009). Many older adults who are raising grandchildren suffer from chronic illnesses and functional limitations that are exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…With rapid population growth due to births and international migration, as well as longer life spans, residential areas are also expanding to accommodate these numbers. From 2016 to 2017, Queensland, Australia experienced the third-largest population increase (79,580 people) of all the Australian states or territories [11]. This study took place in the Moreton Bay region in South East Queensland.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…With rapid population growth due to births and international migration, as well as longer life spans, residential areas are also expanding to accommodate these numbers. From 2016 to 2017, Queensland, Australia experienced the third-largest population increase (79,580 people) of all the Australian states or territories [11]. This study took place in the Moreton Bay region in South East Queensland.…”
Section: Settingmentioning
confidence: 99%
“…can provide support, guidance, and mentorship to the younger generations by drawing on their experiences. Several studies demonstrate that strong intergenerational relationships are not only at the root of healthy and productive aging; they are also important for child and youth development and are a critical component for sustainable societies [9][10][11]. For example, a study of social interactions found that adolescents who worked with an older person on a difficult life problem exhibited more pro-social behavior than adolescents who worked with a peer on a similar problem [12].…”
mentioning
confidence: 99%